Addressing concerns about climate policies: the possibilities and perils of responsive accommodation. Issue 6 (2nd November 2017) - Bullock, Graham; Theodoridis, Alexander G.
ABSTRACT: Responsive accommodation is a political strategy that addresses concerns about a policy proposal by incorporating amendments that address those concerns. This approach can broaden the policy's appeal, but is strategically risky, as it can alienate the policy's base of support. We examine this strategy and its application in the politics of climate change. Using a novel survey experiment, relative public support is evaluated for two amendments to a carbon tax proposal – revenue neutrality assurances and a carbon tariff – designed to ease concerns about taxes and global competitiveness. Analysis shows that support for a carbon tax increases when coupled with a carbon tariff, but decreases among some of the policy's supporters when described as revenue-neutral. These results suggest that policymakers using a responsive accommodation strategy must carefully weigh its possible risks and rewards in their particular context.